Little men : life at Plumfield with Jo's boys - Alcott, Louisa May, 1832-1888. (Boston : Little, Brown, 1983)
Follows the adventures of Jo March and her husband Professor Bhaer as they try to make their school for boys a happy, comfortable, and stimulating place.
Keywords: Boarding schools -- Fiction; Schools -- Fiction; Family life -- New England -- Fiction; New England -- Fiction